An umbrella review and meta-analysis: antimicrobial properties of metal nanoparticles as alternative anti-infective agents for space missions; Acta Astronautica; Vol. 238 - Plotnikov E. V. Evgeny Vladimirovich (2026, 2026)
Title screen